Design of an Educational Application for Conservation and Ornamental Fish Capture Areas Based on Android - Kasmi, Mauli; Kumalasari, Tien; Amir, Syamsul Marlin; Budiman; Usman, Arif Fuddin; Wahyuddin; Ahmad, Ilham; Aman, Andryanto (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
This study aims to develop an educational application centered on the conservation and ornamental fish capture areas in the Pangkajene Islands Regency. Designed for the Android operating system, the application is intended to be user-friendly and accessible to the local community. The testing phase will involve unit testing and compatibility checks to ensure that all functionalities work correctly and that the application performs smoothly across different devices and operating systems. The application will offer detailed information about conservation zones and ornamental fish capture areas within the Pangkajene Islands Regency. It will cover the types of ornamental fish in the region and provide guidelines for protecting the aquatic ecosystem. By delivering this information, the application is expected to be a valuable resource for the community, increasing awareness of the significance of aquatic ecosystem conservation and deepening understanding of ornamental fish conservation practices. This research contributes to the fields of environmental education and technology by creating a digital tool that enhances public awareness and knowledge about local conservation efforts. Utilizing the Android platform ensures broad accessibility, making the information available to a wider audience. Furthermore, the thorough testing processes outlined in this study underscore the importance of application reliability and device compatibility, which are crucial for effective educational content delivery. The research demonstrates how technology can be leveraged to support conservation initiatives, encourage sustainable practices, and aid in biodiversity preservation.